Convergence Theorems for Fixed Points of Multivalued Strictly Pseudocontractive Mappings in Hilbert Spaces - C. E. Chidume; C. O. Chidume; N. Djitté; M. S. Minjibir (Abstract and Applied Analysis)
Let K be a nonempty, closed, and convex subset of a real Hilbert space H. Suppose that T:K→2K is a multivalued strictly pseudocontractive mapping such that F(T)≠∅. A Krasnoselskii-type iteration sequence {xn} is constructed and shown to be an approximate fixed point sequence of T; that is, limn→∞d(xn,Txn)=0 holds. Convergence theorems are also proved under appropriate additional conditions.